2023
DOI: 10.3390/rs15102622
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Biodiversity Assessment Using UAV Lidar and Hyperspectral Data in China’s Pinglu Canal Estuary

Abstract: Mangrove forests are a valuable resource for biological and species diversity, and play a critical role in maintaining biodiversity. However, traditional plant biodiversity survey methods, which rely on labor-intensive field surveys, are not suitable for large-scale continuous spatial observations. To overcome this challenge, we propose an innovative framework for mangrove biodiversity assessment and zoning management based on drone low-altitude remote sensing, integrating data such as vertical structure featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Compared to other remote sensing platforms, UAVs have high temporal and spatial resolution imaging capabilities, which are cost-effective and highly adaptable [60]. Many researchers have confirmed that combining UAV hyperspectral data with LiDAR data can effectively improve inversion accuracy [61,62], which will also be a new trend in studying SPAD inversion.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other remote sensing platforms, UAVs have high temporal and spatial resolution imaging capabilities, which are cost-effective and highly adaptable [60]. Many researchers have confirmed that combining UAV hyperspectral data with LiDAR data can effectively improve inversion accuracy [61,62], which will also be a new trend in studying SPAD inversion.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by species and structural diversity, ecosystem complexity, and spatial and temporal variability, these factors collectively influence the growth of different mangrove species [3][4][5][6]. Analyzing the distribution of species within mangrove ecosystems elucidates their biodiversity by evaluating biomass and carbon storage capacities [7,8]. However, the extent of mangrove ecosystems has gradually diminished in recent years owing to human activities, particularly those associated with agricultural production [9,10].…”
Section: Introductionmentioning
confidence: 99%